Faktor-Faktor yang Berhubungan dengan Capaian Target Imunisasi Dasar Lengkap pada Bayi Di Puskesmas Tanjung Selor Kabupaten Bulungan - Indah, Aisah Puji; Sutrisno, Sutrisno; Gandini, Andi Lis Arming (Media of Health Research, 2023)
Immunization is an effort to actively generate/increase a person's immunity against a disease. The determination of this type of immunization is based on expert studies and epidemiological analysis of the diseases that arise. Providing Complete Basic Immunization (IDL) to infants is a must. In Health Law Number 36 of 2009 it is stated that every child has the right to receive basic immunization in accordance with the provisions. To determine the factors associated with achieving the target of basic immunization for infants at the Tanjung Selor Health Center, Bulungan District. The research design in this study was descriptive analytic with a cross-sectional approach. The research was conducted in September- November 2022. The population in this study were all mothers who had babies aged 1-12 months and lived in the Tanjung Selor Health Center area of 908 people. Determination of the sample using the Non Random Sampling method with Acidental Sampling technique, the number of samples in this study were 90 people. The statistical test used is the Fisher's Exact Test if t count (pvalue) <0.1 is obtained, then the hypothesis Ha is accepted and Ho is rejected. The results of the Fisher's Exact Test on the relationship between distance, family support and support from health workers with the achievement of the complete basic immunization target for infants obtained a pvalue of 0.00. There is a relationship between distance, family support and support from health workers with the achievement of the target of basic immunization for infants in the working area of the Tanjung Selor Health Center with a value of 0.00.